2013
DOI: 10.1103/physrevlett.111.080502
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Josephson Qubit Suitable for Scalable Quantum Integrated Circuits

Abstract: We demonstrate a planar, tunable superconducting qubit with energy relaxation times up to 44 μs. This is achieved by using a geometry designed to both minimize radiative loss and reduce coupling to materials-related defects. At these levels of coherence, we find a fine structure in the qubit energy lifetime as a function of frequency, indicating the presence of a sparse population of incoherent, weakly coupled two-level defects. We elucidate this defect physics by experimentally varying the geometry and by a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
746
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 713 publications
(784 citation statements)
references
References 38 publications
18
746
0
2
Order By: Relevance
“…Variations in T 1 arise predominantly from the qubit interacting incoherently with weakly coupled two-level defects, as discussed in Ref. [1]. In this previous work we found that larger area (with longer and wider legs) Xmon qubits showed higher T 1 values as well as large, frequency-specific suppressions in the energy coherence: for certain frequencies the T 1 would decrease to values below 10 µs.…”
Section: Supplementary Information Device Fundamentals Fabricationmentioning
confidence: 50%
See 3 more Smart Citations
“…Variations in T 1 arise predominantly from the qubit interacting incoherently with weakly coupled two-level defects, as discussed in Ref. [1]. In this previous work we found that larger area (with longer and wider legs) Xmon qubits showed higher T 1 values as well as large, frequency-specific suppressions in the energy coherence: for certain frequencies the T 1 would decrease to values below 10 µs.…”
Section: Supplementary Information Device Fundamentals Fabricationmentioning
confidence: 50%
“…[1], with an important improvement: we have added crossovers to suppress stray microwave chip modes by tying the ground planes together with low impedance connections. Otherwise, the many control wires in our chip could lead to segmentation of the ground plane, and the appearance of parasitic slotline modes [2].…”
Section: Supplementary Information Device Fundamentals Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…1b is a chain of nine qubits, which allows us to experimentally test both first-and second-order fault-tolerance. It consists of a superconducting aluminium film on a sapphire substrate, patterned into Xmon transmon qubits 20 with individual control and readout. The qubits are the cross-shaped devices; they are capacitively coupled to their nearest neighbours, controlled with microwave drive and frequency detuning pulses, and measured with a dispersive readout scheme.…”
mentioning
confidence: 99%